1999
DOI: 10.1038/sj.jhh.1000902
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular pressure-evoked changes in intracellular calcium [Ca2+]i and tone in rat mesenteric and rabbit cerebral arteries in vitro

Abstract: The degree of myogenic response varies between different vascular beds and may contribute to differences in autoregulation. This study examined whether differences in pressure-induced changes in intracellular calcium ([Ca 2؉ ] i ) account for this variability by comparing responses in rabbit cerebral arteries which possess a prominent myogenic response with rat mesenteric arteries where the response is much less marked. Rat mesenteric small arteries and small branches of the posterior cerebral artery were moun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…This indicates that although they do not display a decrease in diameter, they do show active tone development and maintenance of diameter rather than passive dilation. 41,42 Consistent with previous reports, 43 2nd order conduit RMAs did not exhibit active constriction and only dilated passively in response to elevated pressure. However, in the presence of 4-AP or correolide, these vessels maintained a stable diameter with increasing transmural pressure.…”
Section: Plane Et Al Kv1 Channels and Myogenic Contraction 221supporting
confidence: 80%
See 1 more Smart Citation
“…This indicates that although they do not display a decrease in diameter, they do show active tone development and maintenance of diameter rather than passive dilation. 41,42 Consistent with previous reports, 43 2nd order conduit RMAs did not exhibit active constriction and only dilated passively in response to elevated pressure. However, in the presence of 4-AP or correolide, these vessels maintained a stable diameter with increasing transmural pressure.…”
Section: Plane Et Al Kv1 Channels and Myogenic Contraction 221supporting
confidence: 80%
“…For example, cerebral and skeletal muscle arteries show a pronounced decrease in diameter with increasing pressure, 5,41 whereas RMAs of similar diameter do not. 41,42 However, smaller resistance RMAs do show a pressure-induced increase in [Ca 2ϩ ] i similar to that of cerebral vessels 41 and their pressure-diameter curve is flattened at higher pressures (ie, Ն60 mm Hg). This indicates that although they do not display a decrease in diameter, they do show active tone development and maintenance of diameter rather than passive dilation.…”
Section: Plane Et Al Kv1 Channels and Myogenic Contraction 221mentioning
confidence: 99%
“…5). Myogenic contractile responses to increased pressure were not recorded, but it has previously been reported that myogenic responses are less pronounced in mesenteric vessels than in other vascular beds such as cerebral vessels (Coombes et al 1999;Lagaud et al 1999).…”
Section: Mechanical Adequate Stimulusmentioning
confidence: 99%